2022
DOI: 10.1007/s10339-022-01076-3
|View full text |Cite
|
Sign up to set email alerts
|

No effects of transcranial direct current stimulation on visual evoked potential and peak gamma frequency

Abstract: Evidence suggests that the visual evoked potential (VEP) and gamma oscillations elicited by visual stimuli reflect the balance of excitatory and inhibitory (E-I) cortical processes. As tDCS has been shownto modulate E-I balance, the current study investigated whether amplitudes of VEP components (N1 and P2) and peak gamma frequency are modulated by transcranial direct current stimulation (tDCS). Healthy adults underwent two electroencephalography (EEG) recordings while viewing stimuli designed to elicit a robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…Although many studies have reported a-tDCS effects on visual cortex function and plasticity 10 16 , our study is not the first to observe no effect. For instance, while Ding et al 16 and Frase et al 10 demonstrated a modulation of VEP amplitude using a-tDCS, other studies 29 , 30 did not observe such an effect. Abuleil et al 31 observed that tDCS did not modulate binocular rivalry dynamics, while a type of repetitive transcranial magnetic stimulation, namely continuous theta burst stimulation (cTBS), had an effect.…”
Section: Discussionmentioning
confidence: 94%
“…Although many studies have reported a-tDCS effects on visual cortex function and plasticity 10 16 , our study is not the first to observe no effect. For instance, while Ding et al 16 and Frase et al 10 demonstrated a modulation of VEP amplitude using a-tDCS, other studies 29 , 30 did not observe such an effect. Abuleil et al 31 observed that tDCS did not modulate binocular rivalry dynamics, while a type of repetitive transcranial magnetic stimulation, namely continuous theta burst stimulation (cTBS), had an effect.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, as neuromodulational techniques are increasingly used to change the state of the brain, the effect of neuromodulation on peak gamma frequencies was tested. However, the knowledge is still limited: Transcranial alternating current stimulation (tACS) was reported to increase IGF [4,83,84], whereas transcranial direct current stimulation (tDCS) did not modulate IGF [85][86][87]. In addition, non-invasive vagal nerve stimulation was shown to decrease IGF [88].…”
Section: Brain Statesmentioning
confidence: 99%